Efektivitas Discovery Learning Terintegrasi Kearifan Lokal Genteng Karang Penang terhadap Keterampilan Berpikir Kritis Siswa pada Materi Suhu dan Kalor - Badrut Tamam; Suyatno Sutoyo; Dian Novita; Beni Setiawan; Utama Alan Deta (Mataram University, 2026)
This study aims to analyze the effectiveness of Discovery Learning integrated with Karang Penang brick making local wisdom in improving junior high school students' critical thinking skills on temperature and heat topics. This pre-experimental study used a one group pretest posttest design involving 27 students. Data were collected through a validated critical thinking skills test, learning implementation observation sheets, and student response questionnaires, then analyzed using N-Gain and Wilcoxon Signed Rank Tests. The results showed that learning implementation was excellent (83,33%) and student responses were highly positive (89.72%). The improvement in students' critical thinking skills was in the medium category with an N-Gain score of 0.5602. This indicates that developing a Discovery Learning based instructional tool integrated with Karang Penang local wisdom provides a positive contribution to improving students' critical thinking skills. The Wilcoxon test indicated a significant difference between pretest and posttest scores (p < 0.05). In conclusion, implementing Discovery Learning integrated with Karang Penang local wisdom effectively improves students' critical thinking skills.